Probabilistic interval method for phased array sensitivity analysis - Poli, L.; Anselmi, N.; Gottardi, G.; Rocca, P.; Massa, A. (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2016)
This paper presents a novel probabilistic method based on Interval Analysis for predicting the power pattern of a linear array whose element excitation amplitudes are subject to errors. Probabilistic upper and lower bounds of the power pattern have been defined by means of the Interval Arithmetic according to the probability density functions used to model the statistical behavior of the excitation amplitude uncertainties.